Combating Drug Crimes at the East Surabaya Police - Syahrul Qiram (UIN Sunan Gunung Djati, 2022)
The purpose of this study was to determine the extent and magnitude of the influence of drugs in social life and the role of the East Surabaya Police in narrowing the movement of drug syndicates. The research that the author will use in doing this research is research that uses the Juridical Empirical method, namely research on legal identification (unwritten law), intended to find out unwritten law based on applicable law in society. The results of the study can be concluded that in tackling the circulation of narcotics and psychotropic substances, it is necessary to have the participation of all parties and the active participation of the community, especially families, in fostering family members as well as the seriousness and firmness of law enforcers in eradicating, taking action and imposing strict sanctions for perpetrators of narcotics crimes and psychotropic Juridical and non-juridical factors that encourage drug abuse due to economic factors, promiscuity, low level of education, ignorance of the dangers of drug use and legal snares for drug users and dealers